Penerapan Konsep Bawah Laut pada Interior Selam Rekreasi di Surabaya - Gunawan, Edbert (Intra, 2014)
Interior Design of Recreational Scuba Training in Surabaya is a means that aims to meet the needs of the knowledge and training of divers. The background design is Surabaya city does not yet have a dedicated facility for dive training. The scope of this design as an area galleries, stores, cafes, travel, cinema, classroom training, office and support training area. The concept of